Fast pyrolysis of corn stover using ZnCl2: Effect of washing treatment on the furfural yield and solvent extraction of furfural. (August 2015) - Oh, Seung-Jin; Choi, Gyung-Goo; Kim, Joo-Sik
Abstract: To produce a bio-oil having a high concentration of furfural, corn stover was fast-pyrolyzed using ZnCl2 in a fluidized bed reactor at 330–430 °C. The effects of various parameters such as reaction temperature, water- and acid-washing prior to pyrolysis, and ZnCl2 content on the product and furfural yields were investigated. Moreover, solvent extraction was conducted using toluene at different mass ratios of bio-oil/toluene to recover furfural from the obtained bio-oil. The maximum yield of bio-oil was 59 wt%. The bio-oil mainly comprised acetic acid, α-hydroxyketones, and furfural. The maximum furfural yield was 11.5 wt% when the feed material was water-washed, impregnated with 18.5 wt% ZnCl2, and pyrolyzed. Although acid-washing removed alkali and alkaline earth metals much more efficiently than water-washing, water-washing was better than acid-washing for the furfural production. Toluene extraction was very effective to recover furfural from bio-oil. The maximum recovery rate (82%) was achieved at a bio-oil/toluene ratio of 1:4. Highlights: Corn stover pretreated and impregnated with ZnCl2 was successfully pyrolyzed. Furfural was recovered from bio-oil by extraction using toluene. Water-washing was better than acid-washing for the furfural production. The highest furfural yield was 11.5 wt% of the product. The highest furfural recovery rate was 82%.